Predicting delinquent behaviors for Korean youth using the parent–child relationship and career goal tension. Issue 2 (2nd April 2016) - Onifade, Eyitayo; Lee, Jungup; Mennicke, Annelise; Holmes, Jennifer Lynne; Harris, Rachel
ABSTRACT: The purpose of this study was to establish underlying dimensions for variables related to the parent–child relationship and career goal tension in order to create predictor variables. Another goal was to use these subscales to predict delinquent behaviors. Thus, the study assessed the potential differential impact these variables had on delinquent behavior after controlling for gender. The analyses were based on data from the 1st wave of the Korea Youth Panel Survey, and a final sample of 3, 241 youth was utilized. The analysis revealed that there were 5 factor predictors according to the items in each factor: parental attachment, parental stress, parental monitoring, career recommendation, and career discrepancy. Parent–child relationship and career goal tension factors were partially associated with delinquent behaviors for Korean youth. Moreover, those relationships were partially moderated by gender.